Rethinking interdisciplinarity in social sciences: Is it a new revolution or paradox? - Sinha, Chetan (Journal of Interdisciplinary Studies in Education, 2019)
Present paper interrogates and discusses the place of interdisciplinary inquiry in the field of social sciences. The focus is on origination, need and the nature of interdisciplinary inquiry and the emerging movements towards the integration of the disciplines. In addition to looking into the politics of interdisciplinarity, present viewpoint tried to problematize classism, Eurocentrism and dominant meta-theory in the disciplinary constructions, showing the paradox inherent in its formation.